Contagion of Pro- and Anti-Social Behavior among Peers and the Role of Social Proximity - Eugen Dimant (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper uses a novel experimental design to study the contagion of pro- and anti-social behavior and the role of social proximity among peers. Across systematic variations thereof, we find that anti-social behavior is generally more contagious than pro-social behavior. Surprisingly, we also find that social proximity amplifies the contagion of anti-social behavior more strongly than the contagion of pro-social behavior. Anti-social individuals are also most susceptible to the behavioral contagion of other anti-social peers. These findings paired with the methodological contribution inform the design of effective norm-based policy interventions directed at facilitating pro-social behavior and reducing anti-social behavior in social and economic environments.
Keywords: C91; D64; D90; 330; behavioral contagion; peer effects; anti-social & pro-social behavior